(untitled) (American International Journal of Education and Linguistics Research, 2018)
Now a day’s Globalization has become a familiar issue in terms of every area related to human civilization and particularly in the English language. English is the soul media of communication in the modern world and globalization has brought new dimensions in that field. The present study is an attempt to reflect on the contribution f globalization for spreading English language everywhere. During this research one questionnaire has been developed to collect relevant information on the issue. The paper includes analysis on the various contributing factors of globalization.